Female leadership in organisational communication perspective: A systematic literature review - Umar (Faculty of Communications Science, Dr. Soetomo University, 2021)
This systematic literature review aimed to analyse the studies on organisational communication, especially female leadership. The data collection was conducted on Google Scholar, Researchgate, and other reputable journals using the following keywords: “female leadership in organisational communication,” “women, leadership and organisation,” and “organisation, leadership and gender.” From these searches, fifty articles were investigated for the role of female leadership in organisational communication perspective. The result indicates that women can carry out their role as leaders in line with the organisational transformations. As leaders, women must be able to become the main communicator in the organisation. The results also reveal that from the perspective of organisational communication, many female leaders use democratic leadership styles. In terms of Role Theory, we found that female leaders can carry out their roles well, thus positively impacting the organisation.